Gastric Cancer Tumor Microenvironment Characterization Reveals Stromal-Related Gene Signatures Associated With Macrophage Infiltration - Wei, Shenyu; Lu, Jiahua; Lou, Jianying; Shi, Chengwei; Mo, Shaowei; Shao, Yaojian; Ni, Junjie; Zhang, Wu; Cheng, Xiangdong (Frontiers in Genetics, 2020)
Tumor microenvironment (TME) is gaining increasing attention over the last decade for its essential role in tumor initiation, progression and metastasis. With the emergence of immunotherapies in various cancers and its powerful effects, the need for revealing the mechanisms of TME in gastric cancer is more urgent than ever. The aim of this study was to investigate the effect of various components within TME in gastric cancer and reveal the underlying mechanisms with therapeutic potential. Thus, based on immune and stromal components quantified by ESTIMATE algorithm, we sought to explore their relationship and clinicopathological significance in predicting outcomes. Specifically, the low tumor mutational burden and high M2 macrophage infiltration were observed in high stromal group, which are considered immune suppressive characterization and may be responsible for the unfavorable prognosis in gastric cancer (HR = 1.585; 95% CI, 1.112-2.259; P = 0.009). Furthermore, WGCNA analysis, differential expression analysis, univariate Cox analysis and machine learning methods (LASSO and SVM-RFE) were performed to reveal the correlation of genome-wide and immune phenotypic, and eight stromal-relevant genes (FSTL1, RAB31, FBN1, ANTXR1, LRRC32, CTSK, COL5A2, ENG) were identified as adverse prognosis factors in gastric cancer. Finally, via combination of TIMER database and single-sample gene set enrichment analysis (ssGSEA), we found these genes potentially contributes to recruitment of macrophages and polarization of tumor associated macrophages (TAMs). These findings might provide different perspectives into immune microenvironment and could be regard as potential prognosis and therapeutic targets in gastric cancer immunotherapies.